Profile analysis of digital literacy skills of biology education students - Farid, Andi Muhammad Miftah; Zubaidah, Siti; Munzil, Munzil (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
Today's world of higher education emphasizes the importance of digital literacy skills that cannot be underestimated. This study aims to investigate the state of digital literacy among students enrolled in the Biology Education Study Program at Universitas Negeri Malang, focusing on their proficiency in utilizing digital tools and resources, critically evaluating information, and responsibly navigating online domains. The study was a quantitative approach. Questionnaires with a Likert scale consist of 36 statements designed. Data were collected in the even semester of the 2023/2024 academic year from a total of 147 students. The research instrument adapted from validated sources assessed six key indicators of digital literacy (finding, using multiple sources, selecting, evaluating, considering sources effects, and using original work). These quantitative data were analyzed by descriptive analysis technique. The results showed that although most students obtained a moderate level of digital literacy (61.54%), there was a certain number of students with low (1.92%) and very low (0.96%) levels of digital literacy. These results suggest that more attention is needed to digital literacy development in biology education at all levels. These findings emphasized the importance of further and holistic empowerment of digital literacy skills among biology education students, particularly in evaluating and considering the source/effect of messages. Improvements in these areas and studies are critical to preparing students for academic and professional success and fostering their engagement with society in an increasingly digitalized world. Future research efforts should focus on implementing targeted interventions to improve digital literacy in programs and comparing the level of digital literacy across different biology education courses in different institutions. This study contributes to the ongoing discourse on digital literacy in higher education and underscores the need for adaptation and continuous improvement in educational strategies to meet the evolving demands of the digital age.